(untitled) (Eurasian Research Bulletin, 2022)
The article is devoted to game educational technologies and their application in foreign language lessons. The functions and value of game forms of learning in the educational process of a foreign language are revealed. Special attention is paid to the classification of language and speech games. Based on the analysis of existing classifications, the authors propose their own classification, focusing on creative and role-playing games in foreign language lessons.